Study of Islamic Religious Education (PAI) Materials with a Theological Approach - Khoiri Khoiri; Tobroni Tobroni (PT. Anagata Sembagi Education, 2024)
This study aims to examine the application of theological approach in Islamic Religious Education (PAI) materials in Indonesia. The application of theology in PAI curriculum still tends to be limited to normative and ritualistic aspects, while the philosophical and reflective aspects of Islamic teachings are often neglected. Using a descriptive qualitative approach, this study analyzed curriculum documents, syllabi, and PAI textbooks used at the junior high school (SMP) and senior high school (SMA) levels. The results showed that PAI materials focus more on teaching memorization and the performance of worship without exploring the deep meaning of Islamic theological concepts such as tawhid, treatise, shariat, morals, and fiqh. The study also identified challenges in implementing the theological approach, including teachers' lack of understanding of Islamic theology and time constraints in the curriculum. Based on these findings, the study recommends the development of a more integrated curriculum, more in-depth teacher training and the application of more interactive learning methods to enable students to understand Islamic teachings critically and applicatively. This research is expected to contribute to improving the quality of Islamic religious education that is more in-depth and relevant to the challenges of the times